Rules of Planning in Safety Management - Tyrała, Pawel (Communications - Scientific letters of the University of Zilina, 2002)
The article aims to analyze the concept of crisis planning in civil defense system. Strategic plans are worked out by managers of the highest rank and define general aims of the organization. Elements of risk, threads, and ways of activity in crisis situation should be taken into consideration during strategic planning which is the planning of civil defence. Plans for civil defence are worked out in order to assignate and get ready for organizational and material enterprises of civil defence proper to real possibilities. They are prepared by state administration and local governments, factories and other units and institutions which are responsible for preparing and realization of tasks of civil defence. The main aim for working out the plans for civil defence is to get ready appropriate organizational and material enterprises for civil defence in accordance with foreseen threat and needs and real possibilities of the planning rank. The full scope of civil defence tasks of given rank should be given in plans. Providing civil defence formation with technical and military equipment is realized by civil defence inspectorate. Individual protective means against contamination can be bought in regional warehouse of civil defence equipment, while supplementary means should be done individually.